HUBUNGAN PERSONAL HYGIENE DAN SANITASI MAKANAN DENGAN KEBERADAAN SOIL TRANSMITTED HELMINTH DI SELADA (Lactuca sativa) PADA PEDAGANG KEBAB DI MEDAN AREA - LIFEA EFELIANI; IQRINA WIDYA ZAHARA (LP2MTBM MAKARIOZ, 2022)
Soil Transmitted Helminths (STH) is a nematode worm whose life cycle requires soil in order to develop into an infective form. Lettuce is a low plant whose leaf growth is very close to the ground, this vegetable is often consumed in raw conditions or as fresh vegetables so that it has the potential to be contaminated by STH. Several factors such as personal hygiene and food sanitation can affect the occurrence of lettuce contamination of STH eggs. The purpose the research aim to determine whether there is a relationship between personal hygiene and food sanitation with the presence of STH in lettuce (Lactuca sativa) at kebab traders in the Medan Area. The research method is analytic observational with a cross sectional study approach, the sampling method uses a total sampling technique. Research data obtained from primary data using a questionnaire instrument and identification of STH on lettuce using the sedimentation method. Data analysis used univariate test and Fisher's Exact Test. The results were 6 of 30 samples of lettuce (20%) that were positively contaminated with STH, the types of STH found were 3 eggs of A. lumbricoides and 3 larvae of Hookworm. The results of the bivariate analysis between the relationship between personal hygiene and STH contamination were p = 0.501 (P>0.05) and the relationship between food sanitation and STH contamination was p = 0.000 (P<0.05). the conclusion is There is no relationship between personal hygiene and STH contamination in lettuce and there is a relationship between food sanitation and STH contamination in lettuce.